2013
DOI: 10.1007/s11012-013-9796-6
|View full text |Cite
|
Sign up to set email alerts
|

Observations of shear adhesive force and friction of Blatta orientalis on different surfaces

Abstract: The shear adhesive force of four nonclimbing cockroaches (Blatta orientalis Linnaeus, 1758) was investigated by the use of a centrifugal machine, evaluating the shear safety factor (adhesion force divided by body weight) on six surfaces (steel, aluminium, copper, two sandpapers and a common paper sheet) having different roughness. The adhesive system of Blatta orientalis was characterized by means of a field emission scanning electron microscope and the surface roughness was determined by an atomic force micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In the past few years, cockroaches (Blattodea) have become an accepted study object in the field of bioadhesion (e.g. Clemente and Federle, 2008 ; Clemente et al, 2009 ; Lepore et al, 2013 ; Gerhardt et al, 2015 , 2016 ; Betz et al, 2016 ), they possess large smooth adhesive pads and have shown good climbing performance in previous studies (e.g. Roth and Willis, 1952 ; Goldman et al, 2006 ; Clemente and Federle, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, cockroaches (Blattodea) have become an accepted study object in the field of bioadhesion (e.g. Clemente and Federle, 2008 ; Clemente et al, 2009 ; Lepore et al, 2013 ; Gerhardt et al, 2015 , 2016 ; Betz et al, 2016 ), they possess large smooth adhesive pads and have shown good climbing performance in previous studies (e.g. Roth and Willis, 1952 ; Goldman et al, 2006 ; Clemente and Federle, 2008 ).…”
Section: Introductionmentioning
confidence: 99%